A novel endoscopic weight loss therapy using gastric aspiration: results after 6 months - Forssell, Henrik; Norén, Erik (Endoscopy, 2015)
Background and study aims: Obesity is a major public health problem with few effective treatment options. A novel device for treating obesity, the AspireAssist aspiration therapy system, was evaluated. Patients and methods: After 4 weeks taking a very-low-calorie diet, 25 obese men and women (BMI 39.8 ± 0.9 kg/m2) had the AspireAssist gastrostomy tube placed during a gastroscopy. A low-profile valve was installed 14 days later and aspiration of gastric contents was performed approximately 20 minutes after meals three times per day. Cognitive behavioral therapy was also started.Results: At month 6, mean weight lost was 16.5 ± 7.8 kg in the 22 subjects who completed 26 weeks of therapy (P = 0.001). The mean percentage excess weight lost was 40.8 ± 19.8 % (P = 0.001). Two subjects were hospitalized for complications: one subject for pain after gastrostomy tube placement, which was treated with analgesics, and another because of an aseptic intra-abdominal fluid collection 1 day after gastrostomy tube placement. No clinically significant changes in serum potassium or other electrolytes occurred. Conclusion: In this study, substantial weight loss was achieved with few complications using the AspireAssist system, suggesting its potential as an attractive therapeutic device for obese patients. Trial Register ISRCTN 49958132.